2013
DOI: 10.1007/s00726-013-1642-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of amino acids interaction with gold nanoparticle

Abstract: The study of nanomaterial/biomolecule interface is an important emerging field in bionanoscience, and additionally in many biological processes such as hard-tissue growth and cell-surface adhesion. To have a deeper understanding of the amino acids/gold nanoparticle assemblies, the adsorption of these amino acids on the gold nanoparticles (GNPs) has been investigated via molecular dynamics simulation. In these simulations, all the constituent atoms of the nanoparticles were considered to be dynamic. The geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…This is exactly what has been suggested by many authors for this amino acid when it is added in relatively high concentration with respect to the surface Au atoms. Thus our findings do not contradict previous reports not only for Cys but also for other amino acids like those indicating that Asp binds to AuNPs and can act as crosslinking agent . In any case, the different behavior of the amino acids allows the precise identification of five of them (Figure ) at very low concentration (ca., 4 µM).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This is exactly what has been suggested by many authors for this amino acid when it is added in relatively high concentration with respect to the surface Au atoms. Thus our findings do not contradict previous reports not only for Cys but also for other amino acids like those indicating that Asp binds to AuNPs and can act as crosslinking agent . In any case, the different behavior of the amino acids allows the precise identification of five of them (Figure ) at very low concentration (ca., 4 µM).…”
Section: Discussionsupporting
confidence: 68%
“…The presence of typically two or three different functional groups on each amino acid provides a high variability to the possible binding modes between each of them and the surface of gold nanoparticles. Because of this, there is not a unified mode of binding for amino acids to AuNPs as this depends not only on the structure of the single amino acid but also on the experimental conditions and the additional passivating agent present on the nanoparticle surface . The picture is even less clear when the interaction is with small peptides as most of the studies are confined to thiolated systems as those comprising in their sequence cysteine (Cys) or homocysteine, for instance.…”
Section: Introductionmentioning
confidence: 99%
“…In the last paper published by our group we showed mono amino acids conformations after adsorption on the GNP surface [ 9 ]. Our results for Met, Cys, Pro, Phe, Gly and Leu were matched with the experimental results reported by Podstawka et al In the current work we found di and tri- amino acids conformation after adsorption on the gold surface.…”
Section: Resultsmentioning
confidence: 99%
“…GNP kept its cubic shape after 10 ns simulation time. In a previous study by our group, the effect of the size of nanoparticle was examined and it was found that the cubic nanoparticle size makes no difference on the interaction of amino acids [ 9 ]. So in this study GNP size was considered 3 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation